Kajian Empiris Tingkat Akuntabilitas Pemerintah Daerah Dan Kinerja Penyelengara Pemerintah Daerah Terhadap Tingkat Korupsi Pada Kabupaten Dan Kota Di Indonesia - Sucahyo Heriningsih (Jurnal Paradigma, 2014)
This study aims to empirically examine the effect of the level of accountability and performance of the organization of local governments on the level of corruption in the districts and cities in Indonesia. using LPPD in 2010 and LKPD in 2010, with a sample size of 36 counties and cities. Level of Accountability is measured with a variable rate (audit opinion, SPI weakness, and Adherence to legislation) and the implementation of the Local Government Performance (Key Performance Indicators / IKK). Results of regression test show that the measured level of accountability (audit opinion, SPI Weakness level, the degree of compliance with environmental legislation) and the delivery of local government performance (IKK scores of LPPD) did not affect the level of corruption in the government district and city in Indonesia.